Pengaruh Senam Ergonomik Terhadap Perubahan Tekanan Darah Pada Lansia Hipertensi Di Wilayah Kerja Puskesmas Jatibaru Kota Bima Tahun 2019 - Arif Budi Wibowo (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2021)
Hypertension is one of the most common cardiovascular problems in the elderly. Prolonged blood pressure will cause damage to blood vessels throughout the body, so it can be controlled with pharmacological and non-pharmacological therapy, one of them using ergonomics gymnastics. Ergonomics Gymnastics is a movement of gymnastics combined with respiratory technology. The purpose of this research is to know the effect of ergonomics of gymnastics on changes in blood pressure in elderly hypertension in the work area of Puskesmas Jatibaru Kota Bima. Method: This study used quasi-experiment design with pre-post test control group design. About 30 elderly were divided into 15respondents in the intervention group and 15 respondents in control group, which were recruited using purposive sampling. The results of this study showed a significant difference between the intervention and control group in level of blood pressure changes. Based on Wilcoxonsigned rank test in the intervention group obtained pvalue = 0.001 < α 0.05, meaning there is an infulence of ergonomics gymnastyc on blood pressure change in elderly hypertension. For the results of Wilcoxonsigned rank test in control group obtained pvalue = 0.005 < α 0,05, meaning there is influence on weekly program of Puskesmas Jatibaru of the control group on blood pressure change in elderly hypertension. While difference test between treatment and control group using Mann whitney obtain pvalue = 0.004 < 0.05, meaning there is a difference between the intervention and control group in level of blood pressure changes in elderly. Discussion:This research is expected to be considered as the new intervention of Puskesmas Jatibaru to be able to make ergonomics exercise as a hypertensive control program. Conclusion in this study there were sigificant blood pressure changes before and after the nature of ergonomics gymnastyc on elderly hypertension in the work area of Puskesmas Jatibaru Kota Bima.